Entrepreneurial Strategies of Islamic Boarding Schools in Building Economic Independence - Biyati Ahwarumi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study analyzes the entrepreneurial strategies employed by Islamic boarding schools to achieve economic independence, focusing on the case of Sunan Drajat Islamic Boarding Schools in East Java. Framed within the concept of a Sharia-compliant ecosystem, this research utilizes a qualitative case study methodology to investigate the integration of spiritual values with modern business practices. Data were collected through in-depth interviews, direct observation of the Islamic boarding school’s diverse business units, and analysis of institutional documents. The findings reveal a multi-faceted strategy that combines cost leadership, achieved through a cooperative structure, with a differentiation strategy rooted in Islamic principles and community trust. Key success factors include the development of a robust business incubator, a structured santripreneur (santri entrepreneur) development model, and the cultivation of a business ecosystem that emphasizes stakeholder collaboration, professional management, and clear financial accountability. This study contributes a replicable framework for other Islamic boarding schools aiming to build sustainable, Sharia-compliant economic ecosystems, demonstrating that religious institutions can serve as powerful engines for community-based economic development and social empowerment. The model at Sunan Drajat Islamic boarding schools illustrates a successful synthesis of religious values and entrepreneurial acumen, offering significant implications for both theory and practice in Islamic entrepreneurship.